Predictors of Helping Profession Choice and Volunteerism among Siblings of Adults with Mild Intellectual Deficits - Taylor, Julie Lounds (2011)
This study examined aspects of the sibling relationship that predicted altruistic behaviors in siblings of individuals with mild intellectual deficits at three time points in adulthood: in their mid 30s, early 50s, and mid 60s. We identified 393 such siblings from the Wisconsin Longitudinal Study, a prospective longitudinal study that followed participants from ages 18 to 64. Being an only sibling, being older than the brother or sister with mild intellectual deficits, as well as having more contact with and feeling closer to the brother or sister predicted more altruistic behavior in adulthood for female siblings, but not for males. Earlier measures of contact and closeness between siblings were better indicators of altruistic behaviors than concurrent measures.